Manajemen Strategik Bimbingan Manasik dalam Membangun Kemandirian Jemaah Haji Di KBIHU PP Persis - Fau, Fauzidan Wildanul; Nase, Nase; Rustandi, Ridwan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2024)
This study aims to determine the strategy of manasik guidance by KBIHU PP Persis in building the independence of pilgrims, using Fred R. David's Strategic Management Theory (2011). This research uses a qualitative approach, while the method used is a case study. The results show that the strategic management of Hajj Manasik Guidance at KBIHU PP Persis runs according to theory, with the Hisbah Council reviewing the manasik material and centralizing policies. Tiered guidance involves hajj officers, improves quality especially in planning, and contributes importantly to more effective and adaptive guidance practices. This research emphasizes the importance of a strategic management approach in improving the self-reliance of pilgrims.